HUBUNGAN KONSEP DIRI DAN KEMANDIRIAN BELAJAR DENGAN KESIAPAN KERJA SISWA KELAS XI SMK NEGERI 2 PENGASIH - Aditiya Aditiya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
The purpose of this research are to finds: (1) the relationship of self concept with work readiness of the 11st class student in SMK Negeri 2 Pengasih, (2) the relationship of self regulated learning with work readiness of the 11st class student SMK Negeri 2 Pengasih, and (3) the relationship of self concept and self regulated learning with work readiness of the 11st class student SMK Negeri 2 Pengasih. The hypothesis of this research are: (1) true positive and significant relationship between self concept with work readiness of the 11st class student SMK Negeri 2 Pengasih, (2) true positive and significant relationship between self regulated learning with work readiness of the 11st class student SMK Negeri 2 Pengasih, and (3) true positive and significant together relationship between self concept and self regulated learning with work readiness of the 11st class student SMK Negeri 2 Pengasih. The kind of this research is ex-postfacto. The population of this research are 502 students. The method of sample taking over use Slovin formula with 5% significant level so that it got 222 sample member. The technics of sample taking over have done according to precipitate (Simple Random Sampling). The result of this research analyzed with product moment correlation analyse technics for first and second hypothesis, and double analyse technics for third hypothesis. Before hypothesis test have done, firstly do analyse condition test that used normalitas test, linieritas test, and multikolinieritas test. The result of the research show that: (1) directly, self concept has positive and significant relationship with work readiness of the 11st class student SMK Negeri 2 Pengasih that shown with 0,601 correlation coefficient (rx1,y), where 0,601 rhitung > 0,138 rtabel on 5% significant level, (2) directly, self regulated learning has positive and significant relationship with work readiness of the 11st class student SMK Negeri 2 Pengasih that shown with 0,679 correlation coefficient (rx2,y), where 0,679 rhitung > 0,138 rtabel on 5% significant level, and (3) together, self concept and self regulated learning has positive and significant relationship with work readiness of the 11st class student SMK Negeri 2 Pengasih that shown with 0,674 Rhitung and 132,54 Fhitung > 3,04 Ftabel on 5% significant level. That’s means if the self concept and self regulated learning more high so the work readiness high too, likewise the opposite if the self concept and self regulated learning more low so the work readiness low too